Can Extensive Tattoos Make Melanoma Detection More Difficult? Case Report - Rocha, Keyla Borges Ferreira; Oliveira, Cláudia Nunes; de Moraes, Maiara (Brazilian Journal of Case Reports, 2026)
Male patient, 42 years old, skin type I, smoker. He had a lesion on his back for several years, with reports of a nodule appearing on it 6 months ago. The examination revealed a 1.2 cm nodular erythematous violaceous lesion over the right lumbar region of an extensive tattooed area. Dermatoscopy revealed a heterogeneous lesion with flat and nodular components, presenting multiple colors. At the base, there was a brownish, asymmetrical pigmented lesion with an atypical network, inverted network, punctiform vessels, and bright white lines. Over this area, there was an erythematous nodular component with polymorphic vessels and bright white lines, forming a multicomponent pattern. An excisional biopsy with a 2 mm margin was performed, identifying nodular melanoma, Breslow 3 mm.